Virulence studies of Neospora caninum in goat trophoblast primary culture - Álvarez, Betiana Elizabeth (2024)
Neospora caninum is a well-documented cause of abortion in cattle worldwide. The relevance of the abortifacient role of this parasite in small ruminants remains under investigation, especially in areas with high seroprevalence. The objective of this study was to evaluate the virulence (tachyzoite yield [TY] and invasion rate [IR]) of a locally isolated N. caninum strain (NC-Argentina LP1) compared to a reference strain (NC-1) in goat trophoblast cells. Primary culture was obtained from cotyledons of a goat seronegative for N. caninum and Toxoplasma gondii, and negative by PCR, using the explant method. A total of 105placental cells/well (passage 4) were seeded into 24-well plates and grown to confluence (48 hours). For TY and IR studies, cultures were infected with 2x105tachyzoites/well and 104tachyzoites/well of each strain, respectively, in 3 independent assays. At 48 h post infection, TY was quantified by qPCR, and IR was evaluated by immunolabeling of parasitophorous vacuoles (PVs) with anti-N. caninum hyperimmune serum and its conjugate (Alexa Fluor 488, Life Technologies) and DAPI staining. Fifty fields per replicate were counted and PV size was measured. Regarding TY, significant differences were found between NC-Argentina LP1 and NC-1, with lower values for NC-Argentina LP1 compared to NC-1 (p<0.01). In addition, NC-Argentina LP1 showed a lower IR than the reference strain (p<0.0001). However, the size of the PVs was larger for NC-Argentina LP1 with respect to NC-1 (p<0.0001), which could be related to its lower capacity to reinvade. These results suggest that NC-Argentina LP1 can invade and replicate in primary cultures of goat trophoblast, although with lower virulence than the reference strain NC-1, and may aid in predicting in vivo behavior.